Rescattering of stimulated Raman side scattering in nonuniform plasmas - S. Tan; Q. Wang; Y. Chen; W. B. Yao; C. Z. Xiao; J. F. Myatt (Matter and Radiation at Extremes, 2024)
Rescattering of stimulated Raman side scattering (SRSS) is observed for the first time via two-dimensional (2D) particle-in-cell (PIC) simulations. We construct a theoretical model for the rescattering process, which can predict the region of occurrence of mth-order SRSS and estimate its threshold. The rescattering process is identified by the 2D PIC simulations under typical conditions of a direct-drive inertial confinement fusion scheme. Hot electrons produced by second-order SRSS propagate nearly perpendicular to the density gradient and gain nearly the same energy as in first-order SRSS, but there is no cascade acceleration to produce superhot electrons. Parametric studies for a wide range of ignition conditions show that SRSS and associated rescatterings are robust and important processes in inertial confinement fusion.